Effect of Aflatoxin Contaminated Feed for 40 Days on Anatomy and Histopathology of the Thymus of Laying Hens in the Starter Phase - Christy, Rachella; Soeharsono, Soeharsono; Ismudiono, Ismudiono; Eliyani, Hana; Sarmanu, Sarmanu; Plumeriastuti, Hani (Journal of Basic Medical Veterinary, 2021)
The purpose of this study was to determine the effect of aflatoxin contaminated feed given for 40 days on the anatomy and histopathology of the thymus of laying hens in the starter phase. A total of 36 DOC laying hens were divided into two groups (P0 and P1). P0 (control group) was given 100% basal starter feed CP 521 and P1 (treatment group) was given 80% basal feed CP 524 plus 20% aflatoxin contaminated feed. Feeding contaminated with aflatoxin was carried out for 40 days, starting on the 20th to the 60th day after the DOC of laying hens was adapted for 20 days. The time of surgery in this study was carried out on the 20th, 40th, and 60th days, where at each surgery time the thymus organ was taken to collect weight data and histopathological preparations were made. The thymus weights based on time showed a significant decrease, but the intergroup thymus weights did not show a significant decrease. The decrease in thymus weight is caused by the involution process. Microscopic observations based on increased cell debris and congestion showed that P0 did not show a significant difference, but P1 showed a significant difference (p>0.05) on the 40th and 60th days. The conclusion in this study was that as much as 20% of feed contaminated with aflatoxins had not affected changes in thymus weight but had shown damage to the histopathological structure of the thymus.